Penerapan Strategi Team Quiz untuk Meningkatkan Hasil Belajar Mahfudzat Siswa Kelas 2 C Pesantren Al-Madani Cikalong Tahun Ajaran 2024-2025 - Syahrul Hidayat; Haniatul Mabruroh (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study is motivated by the low learning outcomes in Mahfudzat among Grade 2C students at Pondok Pesantren Al-Madani Cikalong, as indicated by an average score of 54.2, which is below the minimum passing standard of 60, as well as low student attention during learning. This study aims to determine the improvement in students’ learning activity and achievement through the implementation of the Team Quiz strategy. The method used is Classroom Action Research (CAR) based on the Kemmis and Taggart model, conducted in three cycles using data collection techniques such as observation, interviews, tests, and documentation. The results show that the Team Quiz strategy is effective in improving both student activity and learning outcomes. Learning activity increased from 84% in Cycle I to 96% in Cycle III, while learning achievement improved from 77% (average score 70) to 100% (average score 86). Therefore, the Team Quiz strategy is proven to enhance the quality of Mahfudzat learning. It is recommended that teachers consistently apply this strategy and that schools provide adequate support to optimize the learning process.